Fractions in the continuing formation of teachers of the early years: Fragments of a complexity - Mocrosky, Luciane Ferreira [UNESP]; Orlovski, Nelem; Tychanowicz, Simone Danielle; Andrade, Salete Pereira; Panossian, Maria Lucia (FapUNIFESP (SciELO), 2019)
This work presents aspects of a qualitative research, of phenomenological approach, developed in the scope of the continuous formation of Mathematics teachers. Here, we present a training bias that recognizes teachers' estrangement as a triggering factor for the formative movement of sixteen teachers, in the theme of fractions as a school content. The analysis is based on the formative possibility of a four-hour meeting, which had as a starting point the perplexities of the teachers when they were asked what is familiar to each one of them when talking about the understanding of fraction. In a phenomenological posture, estrangement stands out as a philosophical attitude that moved the formation, allowing the arising of questions about school content and its teaching. In this perspective, the teachers' realization about the predominance of the technique and formal nomenclatures, with which they were launched to the attribution of fractional meanings, having as proposal the location in a number line. The study revealed the importance of a formation style in which the teacher is called by the anxieties that appear in the dialogue with their peers. Style, which considers the didactic technique, using a reorientation of the way of thinking, feeling and conceiving the world, given the uncertainty of learning each day how to be a teacher.
Frações na Formação Continuada de Professoras dos Anos Iniciais: Fragmentos de uma complexidade
Keywords: Early Years; Fractions; Phenomenology; Teacher Education